Peran Pemerintah Daerah dalam Pemberdayaan Masyarakat di Kampung Wisata Kota Bandung - Afriza, Lia (Manajemen dan Pariwisata, 2024)
Tourism is a field that is currently rising in rank in driving the community’s economic growth. Where the role of the government is to support in encouraging the growth of the community’s empowerment in tourist villages. The aim of the research is to determine the role of the government in encouraging tourism growth in tourist villages in Bandung City. By encouraging involvement in community empowerment and creating policies, they are intended to support the community empowerment in Bandung City tourist villages. The type of research is descriptive qualitative research with data collection techniques using triangulation techniques (interviews, observations, and documentation studies). The result of the research shows that the role of the government based on theories is related to the entrepreneurial indicators, coordination and facilitators have been implemented, however in the process of implementing, the results that was obtained was not optimized. Meanwhile, the community’s empowerment with the dimensions of enabling, empowering, and protecting had also been implemented, but there is still a lack of continuous/periodic supervision and innovation in solving problems that occur in tourist villages. The suggestions to these is to build more participatory programs, to make innovations in solving problems and to increase supervision.